2020
DOI: 10.3390/nu12030670
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration Impairs Physical Growth and Cognitive Development in Young Mice

Abstract: Infancy and childhood are periods of physical and cognitive development that are vulnerable to disruption by dehydration; however, the effects of dehydration on cognitive development during the periods have not yet been fully elucidated. Thus, the present study used a murine model to examine the effects of sustained dehydration on physical growth and cognitive development. Three-week-old C57BL/6J mice were provided either ad libitum (control group) or time-limited (15 min/day; dehydration group) access to wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…In a previous study, our group confirmed that drinking water intake as part of the diet had an important influence on cognitive development by showing that dehydration during infancy resulted in abnormal cognitive development in infant mice [ 3 ]. The present study aimed to determine whether changes in the gut microbiota were associated with cognitive decline in dehydrated mice through the gut-brain axis.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In a previous study, our group confirmed that drinking water intake as part of the diet had an important influence on cognitive development by showing that dehydration during infancy resulted in abnormal cognitive development in infant mice [ 3 ]. The present study aimed to determine whether changes in the gut microbiota were associated with cognitive decline in dehydrated mice through the gut-brain axis.…”
Section: Introductionmentioning
confidence: 86%
“…Adequate water intake is essential for the body’s normal biological and physiological functions [ 1 , 2 ]. Insufficient drinking water consumption during the developmental period is related to various health outcomes, including altered hippocampal gene expression related to cognitive development, abnormal physical growth, and renal development [ 3 , 4 ]. Moreover, not only the water quantity consumed but also the source of drinking water has been considered for their health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Neurobehavioral tests were conducted in the Animal Behavior Facility at the University of Occupational and Environmental Health during the light phase (between 09:00–13:00). Spatial memory was evaluated using the Barnes maze test, a standardized method for assessing spatial memory in rats and mice [ 20 ]. The utilized maze comprised a circular platform (92 cm in diameter) with 20 equally spaced holes around the periphery.…”
Section: Methodsmentioning
confidence: 99%
“…Water restriction. Chronic water restriction was induced for 4 weeks as previously described 58 . Briefly, animals in the RES group were given limited access to water; a water bottle was given to animals for 15 min at the same time each day during the experimental period.…”
Section: Methodsmentioning
confidence: 99%